ISSUES OF SOURCE AND HISTORICAL STUDIES IN THE STUDY OF MIGRATION PROCESSES (Universal International Scientific Journal, 2026)
In the context of globalization, migration processes are expanding and interest in their study is growing. This article aims to analyze sources and shed light on historiography in the study of migration processes. Analysis and synthesis, a systematic approach, and chronological methods were used in writing the article. The coverage of migration theory in foreign literature, the state of demographic history in Uzbekistan during the Soviet years, and changes in the study of this topic during the years of independence were covered.
Keywords: demographic history, migration, labor migration, Pull-push theory.